Composição de cores através da calibração radiométrica e fotométrica de LEDs: Teoria e experimento - Santos, Lucas Fugikawa [UNESP]; Pereira, Clayton José [UNESP] (My University, 2013)
In the present work, the basic concepts of radiometric, photometric and colorimetric calibration are presented, which were applied to three light-emitting diodes (LEDs) used to compose the different color sensations that the human eye perceives in the visible region of the electromagnetic spectrum. In this sense, an experimental setup comprising a LED drive circuit and a home-made integrating sphere was assembled for the initial radiometric and photometric calibration as well as to obtain a set of intensity and spectral combinations associated to different colorimetric CIE (Commission Internationale de l'Eclairage) coordinates. The reader can, therefore, understand, in a simple manner, the process of color composition inside a color monitor or display picture element (pixel ). © Sociedade Brasileira de Física.
Color composition by radiometric and photometric calibration of LEDs: Theory and experiment
Keywords: Cie coordinates; Color composition; Fotometric calibration; Light-emitting diodes; Picture elements; Radiometric calibration